KAJIAN BUSANA TARI REJANG DEWA DI DESA PEDAWA - Sri Utami; I Gusti Agung Malini (Jurnal Da Moda, 2019)
The purpose of this study is to understand and identify the composition of Rejang Pedawa dance attire and the meaning and function of Rejang Pedawa dance outfit. Rejang Pedawa dance fashion is the same as Rejang dance clothing in general but the difference is at the top that uses ungar and sekar spurs made from pelendo that take the form of flowers and tails of peacocks, and the use of traditional Balinese cloth in almost all of the Pedawa rejang clothing. From the functions and meanings it can be concluded that the Rejang Pedawa dance takes a beautiful form because it is indeed the function of the Rejang Pedawa dance to entertain Bhatara Bhatari who is led to descend to Earth during the Pujawali Saba Pedawa Village ceremony. The meaning of Rejang Pedawa's clothing still maintains the fashion that they received from their ancestral heritage. Traditional dance prioritizes a sense of devotion, so it does not take into account too much of the clothing worn.